Militarization going places?: US forces, aid delivery and memories of military coercion in Uganda and Kenya. Issue 2 (4th May 2018) - Bachmann, Jan
ABSTRACT: A number of recent military practices, including contributions to humanitarian relief and reconstruction, as well as counterinsurgency and stability operations, emphasize socio-economic needs of distant populations as one of the key adversaries in this 'era of persistent conflict'. Such developments warrant a critical inquiry into the potential normalization of military approaches to societal issues. The aim of the article is to contribute to current discussions on militarization as a social practice through a study of the involvement of military actors in the delivery of humanitarian assistance and aid in Kenya and Uganda. The article zeroes in on three themes in relation to projects implemented by US civil affairs teams: first, how do military personnel make sense of this 'non-traditional' military practice; second, what are local recipients' expectations about the role of the military in societal issues; and, third, what are potential adversary effects of such 'productive' interventions in contexts that share a memory of military coercion? If we assume that militarization cannot be untied from questions of institutionalized coercion, and if the inquiry to be followed is process- and context-oriented, then attention needs to be directed to potential coercive moments engendered in the context of interventions presented as being benevolent. I assert that it is through a careful study of mundane military practices that we can further add nuance to the concept of militarization in the military-humanitarian realm.